2018
DOI: 10.1093/rpd/ncy029
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Diagnostic Reference Levels for Ct Coronarography in Slovakia

Abstract: The coronary CT angiography (CCTA) is a frequent diagnostic method connected with large variability of effective dose. Therefore, it is the type of examination where optimization is very important and the use of a national diagnostic reference level (DRL) recommended. In Slovakia the DRL for interventional radiology examinations until now fails. The objective of our study was to propose the national DRL for CCTA examinations in Slovak Republic, on the basis of a cross-sectional multicenter study, performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Recent research using ECG-based tube current modulation and dualsource CT coronary angiography revealed radiation dose values ranging from 7 to 9 mSv 13 . In this study, when it represented the effective dose graphically for the two hospitals, it found that the effective doses for males (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) mSv were lower than females (13-29) mSv; this result was presented in Figure-3 for both the hospitals (X) and (Y). This difference in effective doses for males and females may be due to differences in tissue composition and weight.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recent research using ECG-based tube current modulation and dualsource CT coronary angiography revealed radiation dose values ranging from 7 to 9 mSv 13 . In this study, when it represented the effective dose graphically for the two hospitals, it found that the effective doses for males (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) mSv were lower than females (13-29) mSv; this result was presented in Figure-3 for both the hospitals (X) and (Y). This difference in effective doses for males and females may be due to differences in tissue composition and weight.…”
Section: Discussionmentioning
confidence: 72%
“…It has been established that this study has some flaws and must be redone. A follow-up study that takes into consideration more variables, such as the modality of the CT Coronary angiography examination, the value of heart rate during exposure, blood pressure, and more, will be the focus of the effort to provide answers to issues that emerged as a result of our previous findings 15 .CTCA has recently adopted various radiation dose reduction strategies, such as prospective ECG-triggered scanning, heart rate control, lowered tube voltage, and tube current modulation 16 . The British Society of Cardiovascular Imaging and the British Society of Cardiac Computed Tomography performed an audit of radiation exposure, which has led to rapid advances in the decrease of radiation dose from CTCA.…”
Section: Discussionmentioning
confidence: 99%